“The Friend Who Went to Bolivia”: Relations and Contacts Between Argentine and Bolivian Communism During the 1952 Revolution - Martiren, Juan Manuel (Revista de Historia Social y de las Mentalidades, 2025)
The work analyzes the reception of the Bolivian Revolution of 1952 in Argentine communism, as well as the contacts with its Bolivian comrades, through the documents (which had a certain confidential character and were not intended for publication) that emissaries and envoys elaborated for the party organization. The aim is to reconstruct a history of discussions and connections that allows us to observe how the position and characterization of both was processed, while also highlighting the interventions to the Argentine Communist Party (PCA) had in Bolivia. The internationalist character and the regional and transnational structure of communism makes that the perspective proposed here also contributes to recover part of the history of Bolivian communists during a little explored period. It is argued that the views that were put into play were not the same on both sides of the border, and that the PCA helped to structure, not without frictions and problems, the Communist Party of Bolivia (PCB).